How to win friends and influence people - "Carnegie, Dale" (Vermilion London, 1998)
How to Win Friends and Influence People is just as useful today as it was when it was first published, because Dale Carnegie had an understanding of human nature that will never be outdated. Financial success, Carnegie believed, is due 15 percent to professional knowledge and 85 percent to "the ability to express ideas, to assume leadership, and to arouse enthusiasm among people. He teaches these skills through underlying principles of dealing with people so that they feel important and appreciated. He also emphasizes fundamental techniques for handling people without making them feel manipulated. Carnegie says you can make someone want to do what you want them to by seeing the situation from the other person's point of view and "arousing in the other person an eager want. You learn how to make people like you, win people over to your way of thinking, and change people without causing offense or arousing resentment